Volume and Biomass Tables for Farm-grown Malabar Neem (Melia composita Benth.) for Central Plains of Punjab - Gill, R.I.S.; Dhakad, A. K.; Singh, B.; Kaur, N. (Indian Forester, 2025)
The present study was carried out in the central plain region of Punjab state. The data on tree height and diameter at breast height were recorded on Melia composita trees belong to different girth classes and having tree height and DBH ranging from 9.30 m to 19.90 m, and 6.37 to 35.67 cm, respectively. The trees were felled and cut into logs of acceptable merchantable lengths. The data on log length, log diameter on both ends and at mid-point, and log weight were recorded. The volume regression equations were developed to predict the volume table on basis of DBH and tree height (combined variable model), and DBH alone (single-entry model). Results were statistically analysed and found that all equations had very good-fit. Timber volume and biomass predicted by single-entry model (R2 = 0.948) were found quite near to the actual volume and biomass estimated by manual harvesting of the trees but at lower girth class trees. However, combined variable model (R2 = 0.886) was found best fit for the trees belong to upper girth classes for Melia composita plantation. Besides, timber biomass table was developed to get the rough estimation of tree standing biomass so that the farmers can sale their trees at an appropriate price. These tables will be useful to the farmers, timber growers, wood contractors, state forest departments, research workers and the planners for future plantation programmes.